Involvement of scientific societies in the process of higher education governance - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article deals with effectiveness of the impact of the students’ self-governance on the processes of democratization of higher education. The authors identify ways of real involvement of scientific societies in the process of higher education governance and conditions of increasing students’ and postgraduate students’ public activity in the university.